2000
DOI: 10.1007/s005950070009
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdomyosarcoma Presenting as an Anterior Cervical Mass in an Adult: Report of a Case

Abstract: We report herein the case of a 61-year-old man who was referred to our hospital for treatment of a rapidly growing tumor in the right anterior cervical region. A 13 x 14 x 15 cm mass was palpated on physical examination. Computed tomography (CT) findings indicated a thyroid tumor, but cytology results suggested rhabdomyosarcoma. A tumor, measuring 9.3 x 7.2 x 5.2 cm and weighing 220 g, was resected and histopathological examination confirmed a diagnosis of rhabdomyosarcoma. Cervical rhabdomyosarcoma is rarely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…Upon excision of the mass by left hemithyroidectomy, the surgical team noted that there was no normal thyroid tissue remaining in the left side of the neck. This differs from the findings of Tsuchiya et al who reported an adult case of anterior neck RMS of non-thyroid origin which, upon excision, revealed that the ipsilateral lobe of the thyroid had been compressed by tumor and had consequently atrophied [4]. This adult patient had more extensive disease, exemplified by multiple metastatic lesions, compared to the subject of the present case report.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Upon excision of the mass by left hemithyroidectomy, the surgical team noted that there was no normal thyroid tissue remaining in the left side of the neck. This differs from the findings of Tsuchiya et al who reported an adult case of anterior neck RMS of non-thyroid origin which, upon excision, revealed that the ipsilateral lobe of the thyroid had been compressed by tumor and had consequently atrophied [4]. This adult patient had more extensive disease, exemplified by multiple metastatic lesions, compared to the subject of the present case report.…”
Section: Discussioncontrasting
confidence: 85%
“…RMS is essentially a disease of children and young adults with approximately 87% of cases presenting in patients less than fifteen years old and rare reports of cases presenting after twenty-five years of age [1]. Furthermore, 5-10% of RMS cases are reported in infants less than one year of age [1,4]. The incidence of rhabdomyosarcoma shows a slight male predilection with a ratio of about 1.4:1 [1,5].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Rather, it seemed from the clinico‐radiologic profile that the anterior neck and the thyroid were involved by a single malignant tissue bulk, and there was no way to determine the tissue of origin. However, Furze et al noted one case in which rhabdomyosarcoma originating from the anterior neck tissue in an adult failed to invade the thyroid, even when it presented in an advanced stage . This could support the fact the tumor in the present case actually originated from the thyroid itself, rather than the thyroid being invaded.…”
Section: Discussionmentioning
confidence: 48%